PENGARUH TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI TERHADAP PENERIMAAN PAJAK PADA KPP BITUNG - Tuwaidan, Regina Laurensana; Sondakh, Jullie J.; Elim, Inggriani (Universitas Sam Ratulangi, 2013)
State Revenue sources used to funance goverment ecpenditure and development one of which is taxes. Tax revenues indirectly aimed at improving the welfare and prosperity of the community. Thus study aimed to determine the influence of level of private taxpayer to the receipt of income tax article . The duty of Manado Primary Tax Office is to perform the basic tasks of Directorate General Of Taxation in Country?s revenue. This study uses is the analytical method used is simple linier regression statical analysis and also use the secondary data is the tax letter of incoming payment on time and the amount of income tax article payer which is registered in Bitung Primary Tax Office from january 2009 until july 2012. The research results reveals that the level of complience of private taxpayer amount has no significant effect to the receipt of income tax article . This is because they lack the awareness of the public in the Bitung city the importance of paying on time and the tax letter of incoming payment on time there are reports of naught calculation tax.